(untitled) (International Journal of Nursing Education, 2020)
Background: Homelessness is a public health issue across nations. The 2011 Indian national censusestimated 1.77 million men, women and children living without shelter. The US Department of Housing andUrban Development found 567,715 homeless people representing a cross-section of America.Purpose: The purpose of this qualitative descriptive study was to examine the structures, processes andcritical success factors (CSF) of free and volunteer clinics in Kansas City.Methodology: A qualitative research design using a holistic multiple case study method was used toexamine a purposive sample of five safety net clinics in an urban Midwestern state. Data were collectedthrough participant observation and semi-structured interviews. The data were analyzed for common themesthat describe the clinics’ structures, processes and critical success factors.Results: The clinics’ missions, structures, processes and outcomes varied. Mission focus with dignity andrespect and staffing with proper resources and stewardship were the dominant themes. Five subthemes arrivedfrom the narratives: Mission is critical to the viability of the clinic, preserving human dignity, volunteers aretreasured,adapting to meet evolving needs, and money matters.Conclusion: The results suggest that a mission fostering person-centered care, dignity and respect forhumanity impact the success of safety-net clinics, especially for the homeless population. The results willlead in creating a model safety net clinic in Vellore district.